Metaphor Analysis on Students’ English Poems - Irpan Ali Rahman (English Department, Faculty of Education, Universitas Muhammadiyah Jakarta, 2018)
This study aims to know the students’ ability in using a metaphor for their English poems writing. Through the poem, the poet uses the metaphor to sharpen the ideas as the media to express the feeling, thought and life experience. In this case, love poems were written by the fifth-semester students using metaphor. This study uses a qualitative method to gain a description of the metaphor analysis in students’ English love poems. In research findings, the writer found that the students use several kinds of metaphor in semantic perspective and the mystical love metaphor represented in their poems.